Mini Bridge Students Class IV SD Negeri 004 Rambah Samo - Indah, Debby; Sari, Nurtia Nilam (Proceedings of the UR International Conference on Educational Sciences, 2018)
The background of this study is that students have not recognized the mini bridge game, so this research was conducted to increase students knowledge about mini bridges. This research method is a qualitative method.The purpose of this study is to increase students knowledge on mini bridges. The results of this study were (1) students at first did not know at all about the mini bridge, after that the introduction of mini bridges as a brain exercise. (2) to increase students knowledge about mini bridges, basic knowledge of mini bridges was given, before being given basic mini bridge knowledge, the results of the pretest of grade IV students at SD Negeri 004 Rambah Samo was 0% complete and 100% incomplete. After being given basic knowledge about the mini bridge , the results of the posttest were 42% complete and 58% were incomplete. It can be concluded that the introduction and provision of basic knowledge mini bridge can boost student Traffic in understanding mini bridge SD Negeri 004 Rambah Samostudents.